A dose response evaluation of regional incentives to R&D. (18th January 2022) - Spallone, Raffaele; Cerulli, Giovanni
The paper investigates the effects of regional research and development (R&D) incentives granted by the Italian regions in the period 1999-2016 on the performance of the different regional economies. We adopt a continuous treatment model that allows us to analyse the impact of the public support on a series of outcome variables. By studying the shape of the dose response function, i.e., the average treatment effects over all the possible values of the treatment levels, we are able to gauge the impact of public R&D on business performance when the level of the aid intensity changes. By this strategy, we are able to catch differences due a different policy exposure (or 'dose') provided at regional level. In fact, the dose-response approach employed in this study is suited when treatment is continuous, and individuals may react heterogeneously to observable confounders. The empirical analysis is carried out on a novel dataset built on purpose, which consists of a panel covering the whole amount of R&D incentives granted by the Italian regions to business activities between 1999 and 2016. We built our database using data sources made available by the Italian Ministry of Economic Development (MISE).